(untitled) (Asian Journal of Ethnobiology, 2018)
Abstract. Ebenezer A, Ameka GK, Annang TY. 2018. The contribution of modified taunga system to forest cover and livelihoods of forest-fringe communities: a case study of Worobong South Forest Reserve in Ghana. Asian J Ethnobiol 1: 15-30. The purpose of this study was to consider the function of the MTS in assisting forest recovery and in ameliorating the subsistence of peasants within the Worobong South Forest Reserve (WSFR, Akim portion). Geographic Information System (GIS) and Remote Sensing (RS) were utilized to examine the expanse of forest canopy decrease from 1990-2010. The analysis of the involvement of the MTS strategy on forest canopy recovery was also performed by analogizing the natural forest to the MTS plantation by utilizing the 100 m x 100 m square transect techniques and using the Simpson’s Index of Diversity. A socio-economic survey including semi-structured interviews was performed to find out the thinking of the MTS peasants in the Akwansrem, Feyiase, and Miaso communities and forestry officials on forest recovery and the contribution of the MTS to livelihoods of peasants in the study area. The study results showed that the forest canopy in the WSFR had experienced various alterations and/or enhancements, particularly in the closed forest canopy. The jungle canopy declined by 0.41% and 0.17% in 1990-2000 and 2000-2010, respectively. Nevertheless, a principal alteration was examined within the closed canopy in terms of forest vegetation categories. Between 1990-2000, the closed canopy underwent a decline of 45.55%, but it had an increase of 1.25% (41.4 ha) in 2000-2010. It was expected that there would be a further enhancement in the closed canopy in 2010-2020 if the current recovery rate continues to grow. The Simpson’s Index of Diversity showed that the natural forest transect was more diverse (1-D = 0.93) in terms of variety and distribution than the MTS transect (1-D = 0.41). And, stem number was nearly 50% higher than that of the MTS plantation. The research results showed that around 600 to 800 trees were planted by individual peasants annually on 0.8 ha of downgraded lands. The enhancement of closed forest canopy within WSFR was ascribed to the success of the MTS strategy. The results also signified that the subsistence of MTS peasants (concerning their access to livelihoods and farm products and their ability to bear the expense of their children’s education and to construct buildings) had raised. Still, fear of future expectations and continuity of the MTS, unbalanced distribution of MTS farms, wildfires, and illegal logging were several affairs considered impending to the strategy. As a result, several suggestions have emerged. Some of these were: routine evaluation of the contexture and spatial degree of the forest cover to keep track of alterations with the application of GIS and RS; The requirement to explain the directives and advantages of the MTS strategy to farming societies and; the implementation of laws to fulfill the policies that will guarantee continuous management of the forest.